2022
DOI: 10.1097/01.numa.0000829268.46685.bb
|View full text |Cite
|
Sign up to set email alerts
|

Nurse experience during the COVID-19 pandemic

Abstract: Results of a two-question survey of nurses at one hospital identified 5 clear themes related to nurses' experiences during the pandemic and 7 areas for improvement, providing potential strategies for nurse leaders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…They stated that communication with leaders was frequent but confusing. The first-level leadership was supportive, but other levels were non-appreciative 29…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They stated that communication with leaders was frequent but confusing. The first-level leadership was supportive, but other levels were non-appreciative 29…”
Section: Discussionmentioning
confidence: 97%
“…The first-level leadership was supportive, but other levels were non-appreciative. 29 Theme 3 discussed 2 major personal burdens of the pandemic, which included the social distancing effect on family dynamics and cost of social status. First, social distancing helped in cutting the risks of infection but gave birth to negative social consequences such as isolation, loneliness, lack of social interaction, difficulty in finding day/ night care for children, and a distorted way in saying goodbye for the dying beloved ones.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous spread of COVID-19 has aggravated inequalities between demand and supply for nurses as nurses have experienced more burnout. Several studies commonly suggested "the balance between patient and nurse needs satisfaction and exhaustion management" to help ease nurses' burnout experience during the COVID-19 pandemic [Roe, 2022]. In particular, excessive work duties and wearing nearly 3kg-protective equipment were identified to be related to increased fatigue [Liu Q, 2020;Iheduru-Anderson, 2021].…”
Section: Optimization Of Nurse Allocation For Isolation Wardsmentioning
confidence: 99%
“…Competent nursing practice was critically brought to the forefront during the COVID-19 pandemic [14,15]. This rare global pandemic led to the most intense scrutiny of nursing education and preparedness across multiple settings in recent history [16,17]. Nurses' experiences, knowledge, skills, and competency to handle this novel infectious disease have been important topics of discussion in the relevant literature [11,18].…”
Section: Introductionmentioning
confidence: 99%